Systematic Literature Review: Digital Technology-Based Policy Approaches to Improve the Quality and Access of Basic Education in Developing Countries - Hanifah, Hanifah; Arnyana, Ida Bagus Putu; Margunayasa, I Gede (Lembaga KITA, 2025)
This systematic literature review examines digital technology-based policy approaches to enhance the quality and access of primary education in developing countries, a critical issue given the persistent disparities in educational equity and the urgent need for inclusive solutions. Despite the transformative potential of digital technologies, their implementation often fails due to infrastructure deficits, low teacher digital literacy, and contextual barriers. Analyzing 40 peer-reviewed articles (2019–2024), the study reveals a stark policy-implementation gap: while 68% of national policies prioritize infrastructure (e.g., internet connectivity), 70% of local challenges stem from infrastructure gaps and 65% from low teacher readiness. Successful cases, such as China's 85% school digitalization rate, underscore the importance of multi-stakeholder collaboration and balanced budgeting (e.g., 30% infrastructure, 40% teacher training). However, rural areas lag significantly, with only 15% adoption in Albania due to electricity shortages. The findings highlight the limitations of the Technology Acceptance Model (TAM) in addressing contextual challenges such as teacher technophobia (40%) and curriculum misalignment (55%). The study's implications are vital for policymakers: (1) adaptive policies must balance infrastructure investment with human capacity building; (2) hybrid learning models can bridge urban-rural divides, as proven by blended learning's 30–50% participation increase in remote areas; and (3) localized strategies, including culturally responsive teacher training, are essential for equitable adoption. The urban-centric data bias (80%) and pandemic-era context further necessitate longitudinal research in low-resource settings. By advocating for holistic frameworks that integrate infrastructure, pedagogy, and inclusive governance, this review provides a roadmap for sustainable digital education transformation in developing nations